Wpływ nowoczesnych technologii na dystrybucję usług bankowych - Bednarska-Olejniczak, Dorota (The Influence of Modem Technologies on the Distribution of Banking Services, 2007)
Changes of legal regulations, approaching for European Communities, appearance on financial market new players (subjects) and dynamic development of new technology had strong influence on transformations in last years in the Polish bank sector. All of this created the possibility for the Polish banks to introduce and evaluate new products and distributional solution. The main goal of this article is to show influence of modern technology on generation of new distributional channel in banking trade. The article presents the essence of electronic banking trade and it is concentrated on systematizing and characterizing distributional channels which include: cash points, POS terminals, home banking, phone banking, SMS-banking, WAP-banking and internet banking trade.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 113-123